Confederate colonels a biographical register - Allardice, Bruce S. (Shades of blue and gray series., 2008)
"Allardice provides detailed biographical information on 1,583 Confederate colonels, both staff and line officers and members of all armies. In his introduction, he explains how one became a colonel -- the mustering process, election of officers, reorganizing of regiments -- and discusses problems of the nominating process, seniority, and "rank inflation""--Provided by publisher.